The Burden of Living With Cutaneous Lupus Erythematosus - Drenkard, Cristina; Barbour, Kamil E.; Greenlund, Kurt J.; Lim, S. Sam (Frontiers in Medicine, 2022)
Cutaneous lupus erythematosus (CLE) is a group of heterogeneous autoimmune disorders primarily affecting the skin. Patients with these conditions are mostly young women when they become sick and often suffer from recurrent skin symptoms or longstanding changes in their physical appearance. CLE disorders lead to different levels of morbidity and can impact profoundly patients’ quality of life, particularly in the psychological and social health domains. This review provides a summary of recent research investigating the psychosocial burden of living with CLE and the intersect amongst the disease characteristics, patient factors, and social determinants of health. Furthermore, this review provides insight into patient care and research needs that remain unmet to improve the quality of life of patients living with CLE.